Risk Factors Of Type 2 Diabetes Mellitus In The Working Area Of The Kalumata Public Health Center - Lamasila, Ismy Hanifa; Permana, Dini Rahmawati; Marsaoly, Ryan Rinaldy (Fakultas Kedokteran Universitas Malikussaleh, 2025)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia, insulin function, or both. In Indonesia, the number of people with DM reaches 8.5 million, making it the 7th in the world. According to the 2018 Riskesdas report, the prevalence of DM in North Maluku was recorded at 15,381 cases and was the second highest DM case, of which 2,822 cases were found in Ternate City. This study aims to determine the risk factors for type 2 diabetes mellitus in Kalumata Health Center. This study uses a type of quantitative research using case control observational research design, data collection tools in the form of medical records at Kalumata Health Center and primary data using questionnaires, the population of this study were DM and non-DM patients, the sample size of this study was 100 samples, the sampling technique used simple random sampling, this research was conducted in September-December 2024 and the analysis used was chi-square analysis and logistic regression. Of the total 100 samples obtained, the risk factor associated with the incidence of type 2 DM is age with a risk of 0.202 times (p=0.025; 95% CI 0.053-0.768). With this study, it is hoped that it can provide insight into the risk factors for Type 2 Diabetes Mellitus. Thus, the results can be utilized to organize routine counseling.